DAMPAK KURIKULUM MERDEKA BELAJAR TERHADAP KOMPETENSI GURU DALAM PEMBELAJARAN BERBASIS PROYEK DI SD INSAN PRESTASI SCHOOL DENPASAR - Dhesyka Putri , Ni Made Rinka; Redana, Made; Putra Aryana , I Made (UHN IGB Sugriwa Denpasar, 2026)
The Merdeka Curriculum is a varied learning model that focuses on strengthening students’ intracurricular activities with greater time allocation, enabling maximum competency development. The problems discussed in this research are: 1) What is the essence of the obstacles and efforts of the Independent Learning Curriculum in Project-based learning at SD Insan Selamat School?; 2) How does the implementation of the Merdeka Belajar Curriculum meet teacher benchmarks in designing and implementing project-based learning at the Insan Selamat Denpasar Elementary School?; 3) How does the Independent Learning Curriculum impact at the Insan Selamat Denpasar Elementary School contribute to teacher competence in providing project-based learning? This research aims to describe the impact of the Independent Learning Curriculum on Teacher Competence in Project-Based Learning at the Insan Selamat Elementary School, Denpasar. The theories used in this study are hermeneutics, constructivism, and convergence. This study employed a descriptive qualitative research method, with data collection techniques including observation, interviews, documentation, and literature review. Data verification techniques used triangulation of sources, techniques, and time. The results of this study indicate that: 1) The obstacles faced included limited time, differences in student enthusiasm and learning speed, and team collaboration issues. Efforts made to overcome these obstacles included designing a flexible schedule, implementing differentiated learning, grouping students, and assigning clear assignments. 2) The implementation of the Independent Curriculum at Insan Prestasi School Elementary School yielded positive results in designing and implementing project-based learning. 3) The impacts of the Independent Curriculum include positive impacts, such as active student involvement in the learning process, as well as negative impacts, such as complex time management for teachers, differences in student discipline, and responsibilities for group assignments. Keywords: Independent Curriculum, Project-based learning, Teacher competence